2016
DOI: 10.1270/jsbbs.66.281
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous selection for yield-related traits and susceptibility to Fusarium head blight in spring wheat RIL population

Abstract: Fusarium head blight (FHB), caused by the fungal plant pathogen Fusarium, is a fungal disease that occurs in wheat and can cause significant yield and grain quality losses. The present paper examines variation in the resistance of spring wheat lines derived from a cross between Zebra and Saar cultivars. Experiments covering 198 lines and parental cultivars were conducted in three years, in which inoculation with Fusarium culmorum was applied. Resistance levels were estimated by scoring disease symptoms on kern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…FHB, caused by Fusarium culmorum, is a very important disease affecting crops on a global scale [9]. The pathogen is dominant in cooler areas like north, central and western Europe [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FHB, caused by Fusarium culmorum, is a very important disease affecting crops on a global scale [9]. The pathogen is dominant in cooler areas like north, central and western Europe [55].…”
Section: Discussionmentioning
confidence: 99%
“…While the presence of scab can be determined through visual inspection, the presence of DON cannot. Assessment of disease severity is based on the ratio of symptomatic spikelets on each spike and the proportion of infected spikes in tested plants [9]. Although this method is widely used in the screening of resistant germplasms, the results are subjective.…”
Section: Introductionmentioning
confidence: 99%
“…As was shown by Varshney et al (2000), this trait, similarly like the resistance to FHB, is quantitatively inherited and controlled by a number of quantitative trait loci (QTL) distributed on almost all of the wheat chromosomes. Wiśniewska et al (2016) found that in wheat some molecular markers (Xgwm46, Xgwm389, Xgwm533) are associated both with the percentage of Fusariumdamaged kernels and 1000-kernel weight. This indicates that marker-assisted selection for resistance to FHB can be combined with selection for kernel weight.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably caused by the overlap between two influences, i.e. genetic factors conditioning yield-related traits per se, and genetic factors responsible for the reaction to the disease manifested in case of infection (Wiśniewska et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation